2018
DOI: 10.1080/03004430.2018.1425297
|View full text |Cite
|
Sign up to set email alerts
|

Temperament, parental personality and parenting stress in relation to socio-emotional development at 51 months

Abstract: This study examined the relevance of infant temperament, parent personality and parenting stress for children's socio-emotional development, looking in addition for any differences between mothers and fathers. Participants, from a community sample, were 410 mothers and fathers reporting their personality (NEO Personality Inventory), child temperament in the first (Infant Characteristics Questionnaire) and second (Toddler Behavior Assessment Questionnaire) years, parenting stress to 36 months (Parenting Stress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 57 publications
1
8
0
3
Order By: Relevance
“…), as well as aspects that may result in dysfunctional parenting behaviour (i.e., an authoritarian style). Moreover, the present results are in line with those of a recent study on the association between parent personality, parent stress, and child socioemotional development (Ortiz & Barnes, 2018), showing that the children of mothers with low levels of extraversion and greater parent distress were likely to have more internalising problems. Specifically, it seems that parental personality might play an important role in determining the intensity of child emotional and behavioural problems, depending on the personality features of the individual parent (Plotkin et al, 2014), which might, in turn, influence the parents' parenting style and response to stressors.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…), as well as aspects that may result in dysfunctional parenting behaviour (i.e., an authoritarian style). Moreover, the present results are in line with those of a recent study on the association between parent personality, parent stress, and child socioemotional development (Ortiz & Barnes, 2018), showing that the children of mothers with low levels of extraversion and greater parent distress were likely to have more internalising problems. Specifically, it seems that parental personality might play an important role in determining the intensity of child emotional and behavioural problems, depending on the personality features of the individual parent (Plotkin et al, 2014), which might, in turn, influence the parents' parenting style and response to stressors.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, parents with high levels of extraversion (i.e., positive affectivity, energy, sociality) tend to be more talkative, active, social and optimistic, and to enjoy higher well-being and lower levels of parent distress. These parents are typically warm, sensitive and responsive towards their children and engage in high levels of parent-child interaction for the purpose of schooling, play, and emotional support (Ortiz & Barnes, 2018). Indeed, a consistent body of research (for a meta-analysis, see Prinzie et al, 2009) has suggested that personality features can impact parenting quality by promoting or obstructing responsive parenting.…”
mentioning
confidence: 99%
“…Over the last decade, research has identified parental personality as an important contributor that may directly influence children's mental health development (Bertino et al, 2012, Nigg & Hinshaw, 1998, Ortiz Ruiz, 2018, Puff & Renk, 2016. For instance, Bertino et al (2012) found a positive association between parental borderline and antisocial personality patterns and their children's externalizing behaviour problems, with stronger relationships for adolescents than for children.…”
Section: Parental Personality and Adolescent Mental Health Problemsmentioning
confidence: 99%
“…One review by Belsky and Barends (2002) concludes that low parental neuroticism, high parental extraversion, and high parental conscientiousness are most likely beneficial for children's psychosocial development. More recent research has confirmed mothers' high extraversion and high conscientiousness, as significant predictors of children's mental health with lower internalizing problems (Ortiz Ruiz, 2018, Puff & Renk, 2016. However, inconclusive results have been documented for the association between parental agreeableness and openness to new experience and children's mental health (Nigg & Hinshaw, 1998, Oliver et al, 2009, Ortiz Ruiz, 2018, Prinzie et al, 2004.…”
Section: Parental Personality and Adolescent Mental Health Problemsmentioning
confidence: 99%
See 1 more Smart Citation